2024
DOI: 10.3390/medicina60020225
|View full text |Cite
|
Sign up to set email alerts
|

Tirbanibulin 1% Ointment for Actinic Keratosis: Results from a Real-Life Study

Federica Li Pomi,
Mario Vaccaro,
Giovanni Pallio
et al.

Abstract: Background and Objectives: Tirbanibulin 1% ointment is a novel synthetic anti-proliferative agent that inhibits tubulin polymerization. It is approved for treating actinic keratosis (AK) on the face and scalp in adults. It has demonstrated good efficacy, an adequate safety profile and excellent patient adherence in the phase 3 clinical trials, however data about its real-life efficacy and safety are lacking. Here we report the experience of the dermatology unit of the University Hospital of Messina. Materials … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 42 publications
1
1
0
Order By: Relevance
“…In pivotal phase 3 trials, tirbanibulin demonstrated efficacy with CCR achieved in 44–54% of patients and 76–82% of lesions [ 8 ]. These findings were supported also by our real-world data, showing half of the lesions achieving CCR and nearly two-thirds showing PCR [ 14 ]. A recent meta-analysis conducted by Heppt et al demonstrated that tirbanibulin performs with a good safety profile and efficacy, comparable with existing topical treatments currently available in Europe, but with a shorter treatment period which represents its greatest step forward [ 9 ].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…In pivotal phase 3 trials, tirbanibulin demonstrated efficacy with CCR achieved in 44–54% of patients and 76–82% of lesions [ 8 ]. These findings were supported also by our real-world data, showing half of the lesions achieving CCR and nearly two-thirds showing PCR [ 14 ]. A recent meta-analysis conducted by Heppt et al demonstrated that tirbanibulin performs with a good safety profile and efficacy, comparable with existing topical treatments currently available in Europe, but with a shorter treatment period which represents its greatest step forward [ 9 ].…”
Section: Discussionsupporting
confidence: 85%
“…However, although these effects are documented for some AK therapies, they have not yet been explored with the topical application of tirbanibulin 1% ointment. While data about its efficacy and safety profile are already available [ 11 14 ], its impact on photodamage, usually associated with AKs in the context of field cancerization, has recently been reported only in a recent case report [ 15 ]. On this topic, we report a retrospective case series of patients affected by AKs on the face and scalp treated with tirbanibulin 1% in which the topical treatment caused a striking amelioration of concomitant photodamage, with improvement of both wrinkles and solar lentigo.…”
Section: Introductionmentioning
confidence: 99%